2018
DOI: 10.1037/fam0000307
|View full text |Cite
|
Sign up to set email alerts
|

The reliability paradox of the parent–child conflict tactics corporal punishment subscale.

Abstract: In the present investigation we consider and explain an apparent paradox in the measurement of corporal punishment with the Parent-Child Conflict Tactics Scale (CTS-PC): How can it have poor internal consistency and still be reliable? The CTS-PC was administered to a community sample of 453 opposite sex couples who were parents of 3-to 7-year-old children. Internal consistency was marginal, yet item response theory analyses revealed that reliability rose sharply with increasing corporal punishment, exceeding .… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Internal reliability for these items was less than ideal (Cronbach's α = .57). However, research indicates that measures with few items and/or poor internal consistency can be both valid and reliable (Lorber & Slep, ; Zimmerman et al., ). Given the exploratory nature of our research project and the fact that measures with less than ideal internal consistency were related in hypothesized directions to other constructs, we retained this measure in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Internal reliability for these items was less than ideal (Cronbach's α = .57). However, research indicates that measures with few items and/or poor internal consistency can be both valid and reliable (Lorber & Slep, ; Zimmerman et al., ). Given the exploratory nature of our research project and the fact that measures with less than ideal internal consistency were related in hypothesized directions to other constructs, we retained this measure in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Parents who exhibit less extreme aggression (e.g., spanking) most often do not exhibit more extreme forms of aggression (e.g., shaking), although such behaviors clearly all fall within the domain of physical aggression. Thus, α is not reported per Lorber and Slep (2017), who demonstrated that the reliability of this measure is high over much of the range of corporal punishment despite the seeming paradox of its typically low alpha.…”
Section: Methodsmentioning
confidence: 99%
“…Parents/caregivers completed an amended version of the Parent–Child Conflict Tactics Corporal Punishment subscale (CTS-PC; Straus, Hamby, Finkelhor, Moore, & Runyan, 1998). The measure has been shown to have convergent, concurrent, and predictive validity, as well as longitudinal stability (Lorber & Slep, 2018). The CTS-PC Corporal Punishment subscale includes the following behaviors, asked with a 12-month frame of reference: (a) spank on bottom with hand; (b) slap on hand, arm, or leg; (c) hit on bottom with object; (d) slap on face, head, or ears; (e) pinch; and (f) shake; (g) grab was added for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Parents who report fewer extreme acts of corporal punishment (e.g., spanking) most often do not exhibit more extreme forms (e.g., shaking)-negatively affecting alpha-although such behaviors clearly all fall within the domain of physical aggression. The reliability of this measure is high over much of the range of corporal punishment despite the seeming paradox of its typically low alpha (Lorber & Slep, 2018). 2 A multigroup structural equation modeling approach was used to compare females and males on the factor loadings of the CCS scale.…”
Section: Unidimensionality and Factorial Invariancementioning
confidence: 99%